High-mass capabilities of positive-ion and negative-ion direct analysis in real time mass spectrometry: letter - Gross, Jürgen H. (European journal of mass spectrometry, 2016)
Of the ionic liquid 1-butyl-3-methylimidazolium (C+) tricyanomethide (A−) high-mass cluster ions of both positive ([CnAn-1]+) and negative ([Cn-1An]−) charge were generated and detected by direct analysis in real time (DART) Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry (MS). After optimization of the settings of the DART ionization source and of the mass analyser, ions of m/z values unprecedented in DART-MS were detected. Thus, the upper m/z limits of positive-ion and negative-ion DART-MS were substantially expanded. Negative-ion DART-MS delivered cluster ions up to [C15A16]−, m/z 3527 (nominal mass of monoisotopic ion), while positive-ion DART-MS even yielded ions up to [C30A29]+, m/z 6784. The identification of the cluster ions is supported by their accurate mass and exact mass differences corresponding to CA between adjacent cluster ion peaks.
Gesehen am 10.08.2020